Formal diversity and the philosophy of the unit design decorative architectural formations - Abdulhameed Majeed, Oday (Opción, 2019)
The research aims to investigate formal diversity and the philosophy of the unit design decorative architectural formations via comparative qualitative research methods. As a result, the decoration of architecture has a mathematical structure. Mathematics is a logical system and layout in the formations of geometric decoration in Islamic architecture if decoration is a complete form of mathematical thought. In conclusion, the Islamic geometric decoration took its architectural and artistic fields to an astonishing extent, which helped to develop it as a symbolic structure in its geometric or abstract units.